Pengaruh Shopee Paylater, Hari Belanja Online Nasional (Harbolnas), Dan Gaya Hidup Terhadap Perilaku Konsumtif Mahasiswa (Studi Kasus Pada Mahasiswa Fakultas Ekonomi Universitas Negeri Medan) - Habibah, Nurul; Siregar, Zulkarnain (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2025)
This research aims to analyze the influence of Shopee Paylater, national online shopping days and lifestyle on the consumptive behavior of students at the Faculty of Economics, Medan State University. This research uses a quantitative method with a sampling technique of 190 respondents who used Shopee PayLater. The research results show that Shopee PayLater has a positive and significant impact on National Online Shopping Day (Harbolnas). With a P-Value value of 9.297 and a significant value of 0.000. National Online Shopping Day (Harbolnas) has a positive and significant impact on lifestyle. With a significant value of 0.000, the t-statistic value is 14.479. Shopee Paylater has a positive but not significant effect on consumer behavior. With a P-Value of 0.078 while the t-statistic value is 1.764. National Online Shopping Day (Harbolnas) shows a positive and significant influence on consumer behavior. with a P-Value of 0.000 while the t-statistic value is 6.456. Lifestyle has a positive and significant influence on consumer behavior. With a P-Value of 0.000 while the t-statistic value is 4.389. Shopee PayLater has a positive and big impact on lifestyle through national online shopping day (Harbolnas). The t-statistic value is 8.117 and the significant P-Value is 0.000. National online shopping day has a positive and major influence on consumer behavior through lifestyle. The t-statistic value is 4.000 and the significant P-Value is 0.000. Shopee PayLater and Harbolnas have a positive and large influence on consumer behavior. The t-statistic value is 3.943 and the significant P-Value is 0.000. Shopee PayLater has a big, positive influence on consumer behavior during National Holidays. The t-statistic value is 6.129 and the significant P-Value is 0.000.